1988
DOI: 10.1093/sjaf/12.4.275
|View full text |Cite
|
Sign up to set email alerts
|

Eight-Year Performance of Loblolly Pine with Pisolithus Ectomycorrhizae on a Good-Quality Forest Site

Abstract: Loblolly pine (Pinus taeda L) seedlings with different initial amounts of Pisolithus tinctorius (Pt) ectomycorrhizae (Pt index 0, 27, 46, 68, or 88) were planted on a good-quality site (site index 90 ft at age 50) in southwest Georgia. After 8 years and crown closure, trees with Pt indices of 88 and 68 had significantly better survival and greater heights, diameters, volumes, and green weights per tree and per ac than nursery-run, control seedlings (Pt index 0). Volume and weight yields per ac were over 50% gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…As has been reported frequently for pine (Marx & Bryan 1975; Marx et al 1976, 1977b, 1988; Marx & Artman 1979; Ruehle et al 1981; Berry 1982; Valdes 1986; Walker et al 1989; Lamhamedi et al 1992a; Cumming 1993; Walker & Kane 1997) and sometimes for oak (Marx 1979; Dixon et al 1980, 1981a, 1981b; Beckjord et al 1983) in previous studies, Pisolithus tinctorius stimulated shoot growth of sweet birch here as indicated by both dimension and dry weight measurements. This response was evident initially in the seed flats and, perhaps more importantly, later in mine spoil where it persisted for 2.5 years.…”
Section: Discussionsupporting
confidence: 75%
“…As has been reported frequently for pine (Marx & Bryan 1975; Marx et al 1976, 1977b, 1988; Marx & Artman 1979; Ruehle et al 1981; Berry 1982; Valdes 1986; Walker et al 1989; Lamhamedi et al 1992a; Cumming 1993; Walker & Kane 1997) and sometimes for oak (Marx 1979; Dixon et al 1980, 1981a, 1981b; Beckjord et al 1983) in previous studies, Pisolithus tinctorius stimulated shoot growth of sweet birch here as indicated by both dimension and dry weight measurements. This response was evident initially in the seed flats and, perhaps more importantly, later in mine spoil where it persisted for 2.5 years.…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, it is likely that these responses can be attributed to P. tinctorius, as these mycorrhizae were far more numerous on the roots of inoculated seedlings after 18 months in mine soil than after five months in sand culture. Thus, results presented here indicate that this symbiont can stimulate above-ground growth of sweet birch as it has various pine and oak species in an array of previous studies (Marx and Bryan, 1975;Marx et al, 1976Marx et al, , 1977Marx et al, , 1988Marx, 1979;Marx and Artman, 1979;Dixon et al, 1980Dixon et al, , 1981aDixon et al, , 1981bRuehle et al, 1981;Berry, 1982;Beckjord et al, 1983;Valdes, 1986;Walker et al, 1989;Cumming, 1993;Walker and Kane, 1997). Other reports, however, have revealed failures of P. tinctorius in this regard, including those in pine as well as spruce, fir, Douglas-fir, and eucalyptus (Molina, 1979;Grossnickle and Reid, 1982;Riffle and Tinus, 1982;Alvarez and Trappe, 1983;Riffle, 1989;Bougher et al, 1990;Castellano and Trappe, 1991;Cram et al, 1999).…”
Section: Discussionsupporting
confidence: 70%
“…Much of this effort has been directed toward the inoculation of conifers with appropriate ectomycorrhizal symbionts (Marx and Bryan, 1975;Marx et al, 1976Marx et al, , 1977aMarx et al, , 1982Marx et al, , 1984Marx et al, , 1988Marx et al, , 1989aMarx et al, , 1989bTrappe, 1977;Molina, 1979Molina, , 1982Ruehle et al, 1981;Maronek et al, 1982;Riffle and Tinus, 1982;Ruehle, 1982;Molina and Chamard, 1983;Castellano et al, 1985;Perry et al, 1987;Riffle, 1989;Kropp and Langlois, 1990;Castellano, 1994;Repac, 1996;Walker and Kane, 1997;Walker, 2001), while relatively little research has been focused on the development of mycorrhization procedures for hardwoods (Marx, 1979;Dixon et al, 1981aDixon et al, , 1981bDixon et al, , 1985Beckjord et al 1983;Castellano, 1994;Brundrett et al, 1996). A substantial portion of this research, both conifer and hardwood, has involved the mycobiont Pisolithus tinctorius, which is renowned for its broad host range and wide geographic distribution (Marx, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, inoculation stimulates or inhibits growth in the nursery relative to uninoculated plants and these growth differences are carried over into the field (Shaw et al ., 1987; Stenström, 1990; Burgess et al ., 1994). Inoculation effects can last up to 7–10 yr (Marx et al ., 1988; Garbaye & Churin, 1997; Selosse et al ., 2000), sometimes persisting even after the inoculated fungi have disappeared from the root systems (Garbaye et al ., 1988). In other cases, differences in size persist for only 1 or 2 yr after outplanting and then disappear (Hatchell & Marx, 1987; Loopstra et al ., 1988; Cram et al ., 1999).…”
Section: Possible Consequences For Regenerating Stands Of Species mentioning
confidence: 99%